2018
DOI: 10.21831/lt.v5i1.17067
|View full text |Cite
|
Sign up to set email alerts
|

Innovation in the classroom: Engaging English as a foreign learning students using project-based learning

Abstract: Project based learning (PBL) is an instructional approach that focuses on student centre learning, learning process, and students’ autonomy. This study was conducted at International Class Program in one of universities in Salatiga. Furthermore, this study explained the teaching strategies by using project based learning in English drama class. The researcher used a case study as the design and collected the data by using interview and observation. The participants of this study were an English drama lecturer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 2 publications
2
25
0
Order By: Relevance
“…The table above showed that the relationship between project based-learning (as (Musa et al, 2011). In addition, using PBL can give a new atmosphere to increase critical thinking, communication, collaboration, and creativity or 4Cs skills (Karyawati & Ashadi, 2018).…”
Section: Table 3 Correlation Analysismentioning
confidence: 99%
“…The table above showed that the relationship between project based-learning (as (Musa et al, 2011). In addition, using PBL can give a new atmosphere to increase critical thinking, communication, collaboration, and creativity or 4Cs skills (Karyawati & Ashadi, 2018).…”
Section: Table 3 Correlation Analysismentioning
confidence: 99%
“…That is to say, 68% of the participants showed positive attitudes concerning CPBL as a powerful constructional approach that improves cooperation, critical thinking, creativity, and communication skills (Wijayati, Sumarni & Supanti, 2019). These skills are considered crucial for students to be able to compete in the future and effectively analyse, evaluate, and communicate their thoughts or ideas using oral and written communication skills (Karyawati & Ashadi, 2018). CPBL improves students' abilities while also increasing their participation and creative imagination to develop their sense of innovation, which leads to the creation of a bright and smart future (Almulla, 2020).…”
Section: Teachers' Overall Experience In Teaching and Cpbl Implementa...mentioning
confidence: 99%
“…They were creating their drama trailer on social media platforms. Modern digital technology is a major enabler for students to comfortably engage with the process of designing and developing their project as they can document the whole process and easily share their creations in a digital format [17]. The participants from other Department to be interviewed became the source of the data who watched drama performance.…”
Section: B Project Based Learningmentioning
confidence: 99%